Jasminanthes xuanlienensis (Apocynaceae, Asclepiadoideae), a new species from Vietnam - Tran, The Bach (PhytoKeys, 2016)
Abstract. Jasminanthes xuanlienensis (Apocynaceae, Asclepiadoideae), a new species from Vietnam is described, illustrated and compared with its five congeners. Jasminanthes xuanlienensis differs distinctly from congeners by the longer peduncles (14–18 cm vs. 4 cm at most in Jasminanthes pilosa and Jasminanthes saxatilis, salmon-pink color of the inner corolla lobes (white or greenish in the other species), and corolla tube length (12.0–14.5 mm vs. shorter or longer in congeners).